Dengue vaccine development: challenges and prospects - Wilder-Smith, Annelies (Current opinion in infectious diseases, 2022)
Purpose of review - Dengue vaccine development is a high public health priority. To date, no dengue vaccine is in widespread use. Here we review the challenges in dengue development and the latest results for the second-generation dengue vaccines. - Recent findings - The biggest hurdle is the immunological interaction between the four antigenically distinct dengue serotypes. The advantages of second-generation dengue vaccines are the inclusion of nonstructural proteins of the dengue backbone and a more convenient dosing with reduced numbers of doses needed. - Summary - Although dengue-primed individuals can already benefit from vaccination with the first licensed dengue vaccine CYD-TDV, the public health need for the dengue-naive population has not yet been met. The urgent need remains to identify correlates of both protection and enhancement; until such correlates have been identified, all second-generation dengue vaccines still need to go through full phase 3 trials. The 5-year efficacy and safety data for both second-generation dengue vaccines are imminent.